Makna Simbolik Sesaji Tradisi Baritan di Asemdoyong Pemalang Jawa Tengah - Fajrul Falah (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
The purpose of this cultural research is to reveal the symbolic meaning of the Baritan tradition offerings in Asemdoyong, Pemalang, Central Java. The approach used in this research is folklore. The folklore approach is used to reveal the story and symbolic meaning of the tradition Baritan offerings. The research method used in this research is the folklore method which contains three stages of research, analysis, classification, and data analysis. Baritan tradition data collection includes observations (direct and indirect), interviews, questionnaires, and document / library studies. The collected research data is then classified according to the research objectives, namely the category of symbolic meaning of the offerings. After that, the research data were analyzed based on the folklore approach. The results showed the Baritan tradition of expression cultural, and gratitude for the community (fishermen) for the abundant fishing results. This expression is manifested through the offering of food offerings that have positive expectations and meanings. The offering is like a buffalo head (industrious and hard working). Rice is a symbol of prosperity and peace of mind. Traditional snacks (harmony), bananas (useful), and rhombus (acknowledgment and apology).